Murine cytotoxic T lymphocyte recognition of individual influenza virus proteins. High frequency of nonresponder MHC class I alleles (The Rockefeller University Press, 1988)
We determined the MHC restriction of CTL responses to five individual influenza virus proteins. Four viral proteins failed to be recognized in conjunction with three of the five class I alleles of the H-2k and H- 2d haplotypes, while the fifth was recognized only in conjunction with a single allele. This indicates that there is a significant chance that a given class I allele will be associated with low responsiveness or nonresponsiveness for a given foreign protein. This explains, at least in part, why MHC-linked nonresponsiveness is frequently detected in polyclonal antiviral CTL responses. Most importantly, these findings support the idea that responsiveness to foreign antigens is a critical factor in maintaining the high degree of MHC class I polymorphism in outbred populations.